2020
DOI: 10.1175/bams-d-17-0329.1
|View full text |Cite
|
Sign up to set email alerts
|

The MILAN Campaign: Studying Diel Light Effects on the Air–Sea Interface

Abstract: The sea surface microlayer (SML) at the air–sea interface is <1 mm thick, but it is physically, chemically, and biologically distinct from the underlying water and the atmosphere above. Wind-driven turbulence and solar radiation are important drivers of SML physical and biogeochemical properties. Given that the SML is involved in all air–sea exchanges of mass and energy, its response to solar radiation, especially in relation to how it regulates the air–sea exchange of climate-relevant gases and aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 103 publications
4
21
0
Order By: Relevance
“…For the ULW samples, the concentration of ∑PL was between 36.4 and 93.5 µg L -1 , for the SML samples between 61.0 and 118.1 µg L -1 . The measured total lipid concentrations are within the concentration range of the previous measurement studies in different oceanic regions (Frka et al, 2011;Gašparović et al, 2014;Stolle et al, 2019). The lipid classes FFA and phospholipids (PE, PG, PC) dominated within the PL while other lipid classes like TG, HC, ST showed not only a much lower concentration but also much less pronounced variance.…”
Section: Lipids and Lipid Classes In The Particulate Fractionsupporting
confidence: 79%
“…For the ULW samples, the concentration of ∑PL was between 36.4 and 93.5 µg L -1 , for the SML samples between 61.0 and 118.1 µg L -1 . The measured total lipid concentrations are within the concentration range of the previous measurement studies in different oceanic regions (Frka et al, 2011;Gašparović et al, 2014;Stolle et al, 2019). The lipid classes FFA and phospholipids (PE, PG, PC) dominated within the PL while other lipid classes like TG, HC, ST showed not only a much lower concentration but also much less pronounced variance.…”
Section: Lipids and Lipid Classes In The Particulate Fractionsupporting
confidence: 79%
“…For the ULW samples, the concentration of PL was between 36.4 and 93.5 µg L −1 , for the SML samples between 61.0 and 118.1 µg L −1 . The measured total lipid concentrations are within the concentration range of the previous measurement studies in different oceanic regions (Frka et al, 2011;Gašparović et al, 2014;Stolle et al, 2019). Within the PL, the lipid classes FFA (ULW: 5.4-14.0 µg L −1 ; SML: 16.1-36.5 µg L −1 ) and PP (ULW: 15.2-54.9 µg L −1 ; SML: 17.6-37.4 µg L −1 ) had high concentrations in seawater, while other lipid classes such as TG (< 5.8 µg L −1 ) and ST (< 2.4 µg L −1 ) had concentrations lowered by a factor of 4-23.…”
Section: Lipids and Lipid Classes In The Particulate Fractionsupporting
confidence: 73%
“…The results reported here are in agreement with recent laboratory work by Yu et al (2021), who observed little uptake of NO 2 on bulk sea water under dark conditions (γ = 1.6 × 10 −8 ); however, this may not take into account any effect of the organic sea-surface microlayer (SML) on NO 2 heterogeneous conversion. Variability in the observed HONO / NO 2 behaviour overnight may reflect geographical differences in the organic composition of the SML, which will vary in response to changes in local near-term biological activity, underlying surface water composition, anthropogenic inputs, wind speed and solar radiation (see Sabbaghzadeh et al, 2017;Stolle et al, 2020;Wurl et al, 2011;Wurl and Obbard, 2004). The geographical/spatial variability in SML composition is not well known (Engel et al, 2017).…”
Section: Spatial Variability and The Role Of Other Hono Sourcesmentioning
confidence: 99%